Tunnelling of Massive/Massless Bosons from the Apparent Horizon of FRW Universe - Kimet Jusufi; Ali Ovgun; Gordana Apostolovska (Advances in High Energy Physics)
We investigate the Hawking radiation of vector particles from the apparent horizon of a Friedmann-Robertson-Walker (FRW) universe in the framework of quantum tunnelling method. Furthermore we use Proca equation, a relativistic wave equation for a massive/massless spin-1 particle (massless γ photons, weak massive W± and Z0 bosons, strong massless gluons, and ρ and ω mesons) together with a Painlevé space-time metric for the FRW universe. We solve the Proca equation via Hamilton-Jacobi (HJ) equation and the WKB approximation method. We recover the same result for the Hawking temperature associated with vector particles as in the case of scalar and Dirac particles tunnelled from outside to the inside of the apparent horizon in a FRW universe.